The project “Preserve” and the related policy of the Hellenic Ministry of Environment and Energy for the protection of tangible Cultural Heritage - Siountri, Konstantina; Vassi, Avgi; Papadaki, Kalliοpi; Poulou, Maria; Bakoyannis, Efthymios (Technical Annals, 2022)
Nowadays, due to economic crisis, the number of "abandoned", empty or dilapidated listed or historic buildings of Greek cities and settlements is constantly increasing. In order to protect and enhance the Greek tangible cultural heritage, it is necessary to promote actions that give motives to owners or users of historic buildings to preserve them, by providing tools and financial support in the particularly increased costs of restoration and consolidation works of their necessary continuous maintenance. The program “Preserve” introduced by the Hellenic Ministry of Environment and Energy, and more specifically the General Secretariat of Spatial Planning & Urban Environment, relates to interventions in designated as listed or monuments or buildings within historic sites and traditional settlements and historic buildings. The interventions will include facade cleaning (with gentle water jet to remove air pollutants or anti-graffiti painting for protection against vandalism), works in order to preserve the shell of the buildings so as to avoid it’s partial or total collapse, restoration of facades and restoration of the interior of the buildings. Along with the activation of the Digital Land Bank, the Building Rights Transfer, the Single Digital Map, and the Digital Building Identity etc., it will offer the owners of the listed buildings a holistic solution for the protection and enhancement of the tangible cultural heritage of Greece.